Multi-objective optimization on output responses for micro ECM of Al6063 alloy, silicon carbide and boron glass powder metal matrix composites. (2021) - Selvan, T.A.; Madhankumar, S.; Viswanathan, A.; Senthilkumar, K.M.
Abstract: This study investigates the results of a rate of materials dissolution as well as overcut on aluminium 6063 alloy with reinforcement of silicon carbide and boron glass powder. The tests were performed on micro electrochemical machining (ECM) through taking into account various criteria utilising stainless steel as just a substrate. Experimental runs would be designed for the L9 invariant design utilising the Taguchi optimization grey approach with 3 input variables: applied voltage, chloride ability to concentrate and current. Variability method was done to analyse the impact of process variables on the amount of metal matrix composite materials removal rate (MRR) and overcutting of the substance. In addition to the MRR and overcut, the surface roughness (SR) was used as success metrics within that report. At the end, the optimized values of input process variables are identified from grey relational technique. The optimum value was at run 4.